1996
DOI: 10.3892/ijo.8.6.1089
|View full text |Cite
|
Sign up to set email alerts
|

Detection of human papilloma virus (HPV) and K-ras mutations in human lung carcinomas

Abstract: Abstract. The purpose of our study was to assess the prevalence and prognostic significance of HPV infection as well as K-ras codon 12 point mutations in lung cancer. Patients diagnosed with lung carcinoma between 1988 and 1992 (N=99) were selected. HPV detection and typing was performed by PCR from paraffin-embedded tissues, while mutations in codon 12 of K-ras gene were detected using the restriction fragment length polymorphism (RFLP) analysis. The prevalence of HPV infection was 15%, while K-ras codon 12 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
1
10
1
Order By: Relevance
“…But in our study, no difference was found in gender and age. It was similar to the report from Noutsou et al (28) that no correlation was found between HPV infection with sex, age and clinical outcome of the patient, or the histological type and the differentiation grade of the tumor.…”
Section: Discussionsupporting
confidence: 91%
“…But in our study, no difference was found in gender and age. It was similar to the report from Noutsou et al (28) that no correlation was found between HPV infection with sex, age and clinical outcome of the patient, or the histological type and the differentiation grade of the tumor.…”
Section: Discussionsupporting
confidence: 91%
“…In our series, HPV16 has been found in three large cell carcinomas and one poorly differentiated squamous cell carcinoma. The presence of HPV in large cell carcinomas is unusual since it has been reported in only two studies 24,25 with the presence of HPV16 in one case and of HPV31-33 in two cases. Of particular interest is the absence of koilocytes in all our positive cases.…”
Section: Discussionmentioning
confidence: 92%
“…Since Noutsou et al (36) pointed out the involvement of highrisk HPVs in the carcinogenesis of the lung in cooperation with K-Ras mutation, it is worthwhile to examine the frequency of K-Ras mutation in HPV-positive and -negative lung carcinomas.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%